Usefulness of Arthroscopic Treatment of Painful Hip after Acetabular Fracture or Hip Dislocation - Hwang, Jung-Taek; Lee, Woo-Yong; Kang, Chan; Hwang, Deuk-Soo; Kim, Dong-Yeol; Zheng, Long (Clinics in orthopedic surgery, 2015)
Painful hip following hip dislocation or acetabular fracture can be an important signal for early degeneration and progression to osteoarthritis due to intraarticular pathology. However, there is limited literature discussing the use of arthroscopy for the treatment of painful hip. The purpose of this retrospective study was to analyze the effectiveness and benefit of arthroscopic treatment for patients with a painful hip after major trauma. From July 2003 to February 2013, we reviewed 13 patients who underwent arthroscopic treatment after acetabular fracture or hip dislocation and were followed up for a minimum of 2 postoperative years. The degree of osteoarthritis based on the Tonnis classification pre- and postoperatively at final follow-up was determined. Clinical outcomes were evaluated using visual analogue scale for pain (VAS) and modified Harris hip score (MHHS), and range of motion (ROM) of the hip pre- and postoperatively at final follow-up. There were nine male and four female patients with a mean age at surgery of 28 years (range, 20 to 50 years). The mean follow-up period of the patients was 59.8 months (range, 24 to 115 months), and the mean interval between initial trauma and arthroscopic treatment was 40.8 months (range, 1 to 144 months). At the final follow-up, VAS and MHHS improved significantly from 6.3 and 53.4 to 3.0 and 88.3, respectively (p = 0.002 and p < 0.001, respectively). However, there were no significant differences in hip flexion, abduction, adduction, external rotation, and internal rotation as minor improvements from 113.1°, 38.5°, 28.5°, 36.5°, and 22.7° to 118.5°, 39.0°, 29.2°, 38.9°, and 26.5° were observed, respectively (p = 0.070, p = 0.414, p = 0.317, p = 0.084, and p = 0.136, respectively). None of the patients exhibited progression of osteoarthritis of the hip at the final follow-up. Arthroscopic treatment after acetabular fracture or hip dislocation is effective and delays the progression of traumatic osteoarthritis.